Literasi Keuangan Berbasis Nilai Islami: Membangun Generasi Mandiri dan Berdaya Saing - Rosalina, Eka; Endrawati, Endrawati; Ramadhea Jr, Syafira; Oliyan, Fitra; Santi, Elfitri; Djefris, Dedy; Gustina, Gustina; Handayani, Desi (-, 2025)
This community service activity by the Accounting Department of Padang State Polytechnic aims to integrate Islamic financial principles into financial literacy programs, with the hope of shaping a young generation that is not only financially savvy, but also grounded in Islamic moral values and ethics, because many students do not yet have a deep understanding of Islamic financial principles, including aspects of halal-haram and usury. In daily practice, students are often involved in transactions that do not align with Sharia principles, either due to a lack of knowledge or economic temptation. To overcome this problem, the community service team provided training to students at the Al-Ma'arif Bukittinggi Modern Islamic Boarding School, which focused on theoretical learning about Islamic finance, using methods such as lectures, group discussions, transaction simulations, quizzes, and periodic evaluations of Islamic financial literacy. As a result of this training, students' understanding increased by 8% from 46% to 54%, which means that this community service activity was able to foster and create a good understanding among students regarding financial practices in Islam.